INFLUENCE OF COMMUNICATION, DISCIPLINE, COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE WORK PRODUCTIVITY AT PT. STEEL FACILITIES STUDIES IN THE CITY OF SAMARINDA - Askiah Askiah; Fenty Fauziah; Azi Nur Rahmasita; Joko Sabtohadi (Sean Institute, 2022)
The purposes of this study are 1) To determine the effect of work communication on employee productivity. 2) Knowing the effect of work discipline on employee work productivity. 3) Knowing the effect of compensation on employee productivity. 4) Knowing the effect of the work environment on employee work productivity. Data collection techniques used a questionnaire to 50 employees of PT Sanggar Sarana Baja in the city of Samarinda. The data were analysed using the SPSS version 24 application program. The results found that 1) Indicating that the influence of work communication variables on work productivity has a positive and significant relationship. 2) Shows that the effect of the work discipline variable on work productivity has a positive and significant relationship. 3) Shows that the effect of compensation variable on work productivity has a positive and significant relationship. 4) Shows that the effect of work environment variables on work productivity has a positive and significant relationship.